ANALISIS KEKERASAN SOSIAL DALAM NOVEL “KERLING SI JANDA” KARYA TAUFIQURRAHMAN AL-AZYZI - Erna Lesmana; Ayep Wahyudin; Eli Syarifah Aeni (IKIP Siliwangi, 2019)
This study aims to (1) analyze the social violence contained in the novel